2016
DOI: 10.1177/2333794x15623243
|View full text |Cite
|
Sign up to set email alerts
|

Acute Poisoning in Children in Bahia, Brazil

Abstract: Acute poisoning is a frequent accident in childhood, particularly in children under 4 years of age. This was a descriptive study with data collected from standardized forms of the Poison Control Center and patient record charts. All the cases of acute poisoning in children aged 0 to 14 years during the period 2008 to 2012 were selected. The variables studied comprised characteristics of the events and toxic agents, clinical development, and outcome. A total of 657 cases of acute poisoning, with higher frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
4
14
1
Order By: Relevance
“…Interestingly, our series lacks the second peak in children aged 10-14 ( Fig. 1b): we report a 2.3% of suicide attempts, a low percentage if compared with other studies [10,11,15,[18][19][20]. Nevertheless, the small rate of suicides found in our study might be influenced by the upper age limit of the population considered, which reaches up to 14 years.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Interestingly, our series lacks the second peak in children aged 10-14 ( Fig. 1b): we report a 2.3% of suicide attempts, a low percentage if compared with other studies [10,11,15,[18][19][20]. Nevertheless, the small rate of suicides found in our study might be influenced by the upper age limit of the population considered, which reaches up to 14 years.…”
Section: Discussioncontrasting
confidence: 59%
“…Notably, no hospitalization in the pediatric intensive care unit and no deaths were recorded in our series: to the best of our knowledge only two other papers published in 2019 reported no deaths [2,13]; many other previous studies worldwide declared at least some cases [4,7,12,15,18,19,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…12 Better outcome is related to earlier presentation in emergency. In our study, poison ingestion was accidental in 87.8 % of the cases which is comparable to those reported by Mendonca et al 8 We found that poisoning agent was located at home in 81.1% of the cases. Home is the place where children spend most of their time before school going age so it becomes the place with greater number of mishaps including poisoning.…”
Section: Discussionsupporting
confidence: 90%
“…less family care and vigilance for male children leading to increased liberty in their routine activities with lesser supervision. 8 Majority of the cases was between 13-59 months of age followed by 5-10 years of age. In previous studies, acute poisoning has been observed more in children aged up to 5 years and peak at 2 to 3 years of age.…”
Section: Discussionmentioning
confidence: 98%